2020
DOI: 10.1038/s41567-019-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynein harnesses active fluctuations of microtubules for faster movement

Abstract: Motor proteins take part in the organization and division of eukaryotic cells by using their ability to move unidirectionally along the cytoskeletal tracks. While kinesin and myosin motor families have members that move towards either end of actin and microtubules, respectively, all dynein motors exclusively move towards the minus-end of microtubules. Previous studies reported that dynein asymmetrically responds to external forces, moving faster when pulled forward, while resisting backward movement under hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 128 publications
(244 reference statements)
3
33
1
Order By: Relevance
“…While a recent study modeled the apo-state bond behavior of a single S. cerevisiae dynein head as an asymmetric slip bond for forces up to 14 pN 65 , a closer look at the measured data shows an excellent agreement with our results for forces up to ~5 pN, including the slip bonding up to ~2 pN and an ideal bonding up to ~5 pN under backward load. Our data also suggest an increasing unbinding rate above ~5 pN so that the bond appears best described by an overall slip-ideal-slip behavior for the 0–10 pN force range (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…While a recent study modeled the apo-state bond behavior of a single S. cerevisiae dynein head as an asymmetric slip bond for forces up to 14 pN 65 , a closer look at the measured data shows an excellent agreement with our results for forces up to ~5 pN, including the slip bonding up to ~2 pN and an ideal bonding up to ~5 pN under backward load. Our data also suggest an increasing unbinding rate above ~5 pN so that the bond appears best described by an overall slip-ideal-slip behavior for the 0–10 pN force range (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study reported that a single S. cerevisiae dynein head exhibited slipbonding in both MT directions 77 . Although the authors confirmed that the unbinding rate in the backward direction increased more slowly than in the forward direction 38,58,66,78 , the unbinding rates increased exponentially.…”
Section: Discussionmentioning
confidence: 99%
“…3 & 4). As we have already discussed 38 , the reason for this discrepancy is primarily due to the different unbinding-force assays that were used: while Ezber et al 77 used the "oscillatory assay" where the trap rapidly switched between two positions 66 , we used the "constant-pulling assay" where a MT attached to a coverslip moved at a constant velocity past the stationary trapped bead 38,58,79 . Extremely high loading rates up to ~25,000 pN/s can develop in the oscillation assay 38 ; therefore, it is possible that the high loading rates affect the dynein-MT bond and contribute to increased unbinding rates with larger forces.…”
Section: Discussionmentioning
confidence: 99%
“…The present model can be extended to study the effects of the vectorial character of the applied load on the mechanics of dynein and myosin motors, since the load-velocity and -detachment rate behaviours of kinesins, dyneins, and myosins are similar [14][15][16][17]. This can help to understand the mechanics of collective function of different molecular motors, owing to the force-dependent interactions of the motors.…”
Section: (C) and 3(b)mentioning
confidence: 93%
“…They measured the vertical load component F z , where the horizontal component F x was resisting (<0, applied against the stepping direction). More recently, single-molecule optical trapping experiments [14][15][16][17] have studied the function of molecular motors under assisting loads F x (>0, applied in the stepping direction) as well. They have shown that the motors exhibit similar responses to the applied load direction: i) their velocity decreases with resisting loads, but changes slightly when the load is assisting, and ii) motors favor faster detachment rate under assisting loads than resisting ones.…”
Section: Introductionmentioning
confidence: 99%